Tuning anion solvation energetics enhances potassium–oxygen battery performance - Sankarasubramanian, Shrihari (Proc Natl Acad Sci U S A, 2019)
The oxygen reduction reaction (ORR) is a critical reaction in secondary batteries based on alkali metal chemistries. The nonaqueous electrolyte mediates ion and oxygen transport and determines the heterogeneous charge transfer rates by controlling the nature and degree of solvation. This study shows that the solvent reorganization energy (λ) correlates well with the oxygen diffusion coefficient [Formula: see text] and with the ORR rate constant [Formula: see text] in nonaqueous Li–, Na–, and K–O(2) cells, thereby elucidating the impact of variations in the solvation shell on the ORR. Increasing cation size (from Li(+) to K(+)) doubled [Formula: see text] , indicating an increased sensitivity of [Formula: see text] to the choice of anion, while variations in [Formula: see text] were minimal over this cation size range. At the level of a symmetric K–O(2) cell, both the formation of solvent-separated ion pairs [K(+)–(DMSO)(n)–ClO(4)(−) + (DMSO)(m)–ClO(4)(−)] and the anions being unsolvated (in case of PF(6)(−)) lowered ORR activation barriers with a 200-mV lower overpotential for the PF(6)(−) and ClO(4)(−) electrolytes compared with OTf(−) and TFSI(−) electrolytes with partial anion solvation [predominantly K(+)–(DMSO)(n)–OTf(−)]. Balancing transport and kinetic requirements, KPF(6) in DMSO is identified as a promising electrolyte for K–O(2) batteries.